Influence of match location in the spanish Copa del Rey (Efecto localización en la Copa del Rey del fútbol español) - Pic Aguilar, Miguel; Castellano Paulís, Julen (Retos, 2017)
This research studies second leg home advantage in football. Spanish Copa del Rey football eighth-finals (round of 16), quarter-finals (round of 8) and semi-finals (round of 4) from 1940-41 to 2013-14 have been analyzed, adding up to 2056 matches and 1028 play-offs. A non-parametric binomial contrast was applied to determine the influence of playing at home, while a binary logistic regression was used to show the explanatory proportion of goals after winning the qualifying round following the first confrontation. The results confirmed significant differences between playing as local or visitor (location) in the first or second match of the tie. Learning to manage the goals margin according to location with possible consequences on the selection of the more appropriate playing model, among others, suggest the specificity of this competition system. These results can help trainers to get a more ecological design of tasks with the real situation of matches.Resumen. Esta investigación estudia la ventaja de jugar en casa eliminatorias de ida y vuelta en fútbol. Fueron analizadas eliminatorias de octavos de final, cuartos de final y semifinales de la Copa del Rey desde 1940-41 hasta 2013-14, sumando un total 2056 partidos y 1028 eliminatorias. Se aplicó un contraste no paramétrico binomial para conocer la influencia de jugar en casa, mientras que una regresión logística binaria fue empleada para conocer la proporción explicativa de los goles al pasar la eliminatoria tras el primer enfrentamiento. Los resultados confirmaron diferencias significativas entre jugar como local o visitante (localización) en el primer o segundo partido de la eliminatoria. Aprender a gestionar el margen de goles según localización con posibles consecuencias sobre la selección del modelo más apropiado de juego, entre otras, sugieren de la especificidad de este modelo de competición. Estos resultados pueden ayudar a preparadores para conseguir un diseño de tareas más ecológico con la situación real de los partidos.